Smart Battery Management Technology in Electric Vehicle Applications: Analytical and Technical Assessment toward Emerging Future Directions - Hossain Lipu M.S.; Miah M.S.; Ansari S.; Wali S.B.; Jamal T.; Elavarasan R.M.; Kumar S.; Naushad Ali M.M.; Sarker M.R.; Aljanad A.; Tan N.M.L. (MDPI, 2023)
Automotive industry; Battery storage; Charging (batteries); Deterioration; Electric vehicles; Equalizers; Lithium-ion batteries; Sustainable development; Temperature control; Thermal management (electronics); Analytical analysis; Battery equalization; Battery Management; Battery storage; Battery thermal managements; Management technologies; State of health; States of charges; Technical assessment; Vehicle applications; Battery management systems